Pay suppression in social impact contexts: How framing work around the greater good inhibits job candidate compensation demands - HUSSAIN, Insiya (Institutional Knowledge at Singapore Management University, 2024)
Past research suggests that when organizations communicate the benefits of their work for human welfare—that is, use a social impact framing for work—job candidates are willing to accept lower wages because they expect the work to be personally meaningful. We argue that this explanation overlooks a less socially desirable mechanism by which social impact framing leads to lower compensation demands: the perception among job candidates that requesting higher pay will breach organizational expectations to value work for its intrinsic (rather than extrinsic) rewards, or constitute a motivational norm violation. We find evidence for our theory across five studies: a qualitative study (Study 1), a hiring experiment with undergraduate students (Study 2), an online labor market field experiment (Study 3), a vignette-based simulation (Study 4), and a stimulus sampling study using multiple occupations (Study 5). Exploratory analyses find that the negative effects are unique to monetary (versus nonmonetary) job rewards. Together, results uncover a novel mechanism by which emphasizing work for the greater good leads job candidates to accept lower wages—one that reflects candidates self-censoring on pay from concerns about violating organizational norms rather than solely from a willingness to trade higher pay for potentially meaningful work. Our research contributes to understandings of how social responsibility messaging impacts workers’ perceptions of organizations and negotiation behavior. It also holds implications for emerging scholarship on managers’ implicit theories of employee work motivation.